2005
DOI: 10.1080/10236660500479478
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Maleic Acid Grafted Chitosan

Abstract: Modification of chitosan (CHI) with maleic acid (MA) via maleic anhydride (MAn) was investigated in acetic acid solution, in the presence of cerium ammonium nitrate (CAN) as the initiator. The effects of reaction time, temperature, and CAN and MA concentrations on the grafting percentage were studied. The products were characterized by Fourier-transform infrared, differential scanning calorimetry, and 13 C NMR, in addition to gravimetric evidence to grafting. A maximum of 105% grafting was achieved under the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(5 citation statements)
references
References 12 publications
(9 reference statements)
0
5
0
Order By: Relevance
“…For PGM-CHO and PGM-MA, this peak is sharper and has a higher intensity compared to the shoulder peaks of PGM and PGM-COOH, thus suggesting the existence of aldehydes mainly in the PGM-CHO and PGM-MA, whereas in PGM (before the first oxidation) and PGM-COOH (after the second oxidation of aldehydes to carboxylic acid), there is no substantial presence of aldehydes . After maleylation (PGM-MA), a new amide II peak appears at 1575 cm –1 corresponding to the C–N and N–H stretching in PGM-MA . The peaks at 1421 and 1344 cm –1 are correlated with the O–H bending and C–O stretching of maleic acids, respectively.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…For PGM-CHO and PGM-MA, this peak is sharper and has a higher intensity compared to the shoulder peaks of PGM and PGM-COOH, thus suggesting the existence of aldehydes mainly in the PGM-CHO and PGM-MA, whereas in PGM (before the first oxidation) and PGM-COOH (after the second oxidation of aldehydes to carboxylic acid), there is no substantial presence of aldehydes . After maleylation (PGM-MA), a new amide II peak appears at 1575 cm –1 corresponding to the C–N and N–H stretching in PGM-MA . The peaks at 1421 and 1344 cm –1 are correlated with the O–H bending and C–O stretching of maleic acids, respectively.…”
Section: Resultsmentioning
confidence: 98%
“…37 After maleylation (PGM-MA), a new amide II peak appears at 1575 cm −1 corresponding to the C−N and N−H stretching in PGM-MA. 55 The peaks at 1421 and 1344 cm −1 are correlated with the O−H bending and C−O stretching of maleic acids, respectively. As for the different free-standing PGM films (Figure S2), the appearance of amide I and II peaks suggests that the protein structure remains intact after crosslinking.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…As shown in Figure 2, the absorption peak at the wavelength of 3448.72 cm -1 presented in the spectra of MCS attribute to stretching vibration of -OH and -NH 2 which is overlapping , meanwhile weak absorption at 2931.80 cm -1 wavelength correspond to stretching vibration of C-H [23], [28] . Moreover, at 825.53 cm -1 is attributed to C = C groups in maleoyl [13], [29]. Hence, the characterisation by FTIR revealed that the synthesised compound is N-maleoyl chitosan (MCS).…”
Section: Ftir Analysismentioning
confidence: 99%
“…A number of studies revealed that for pure PVP, the bands observed at 2924 cm −1 and 2892 cm −1 , 1664 cm −1 , 1461 cm −1 , and 962 cm −1 were attributed to CH 2 symmetric stretching, -C=O and C=C stretching, CH 2 bending, and out-of-plane ring C-H bending, respectively and another band obtained at 1286 cm −1 showed characteristic vibrations of C-N in PVP. The spectra for CA and CA-S1 to CA-S5 membranes showed strong peaks at 1659 cm −1 , which confirmed the presence of PVP in each blend [25,26]. A small new peak observed at 1714 cm −1 indicated the C=O vibrations of maleic acid, and the peaks shown at 827 cm −1 and 796 cm −1 are attributed to C-H rocking of the olefinic structure, confirming the incorporation of maleic acid on to the CS backbone [27].…”
Section: Ftir Analysismentioning
confidence: 88%